PERGESERAN CITRA WANITA MINANGKABAU: DARI KONSEPSI IDEAL-TRADISIONAL KE REALITAS - Erianjoni Erianjoni (Universitas Islam Negeri Imam Bonjol Padang, 2011)
This article discusses how the Minangkabau ethnic women undergoing a transformation that relates the image of women seen from the traditional conception of the ideal and changes in today’s reality. In this article reveals made many changes since the entry of women into the public sector leaving the domestic sector, form education and urbanization. Keywords : Minangkabau Women and transformatianCopyright © 2011 by Kafa`ah All right reservedDOI : 10.15548/jk.v1i2.80